Effects of Different Forms of Organic Selenium on Growth Performance, Antioxidant Capacity, and Intestinal Health in Rice Field Eel (Monopterus albus) - Denghang Yu; Yujia Liu; Jincheng Wan; Jiaxiang Chen; Yangjie Qiu; Chi Zhang (Animals)
To evaluate the effects of different organic selenium sources on rice field eel (Monopterus albus), four isonitrogenous and isolipidic diets were tested: a control (no supplement) and four diets each supplemented with 0.24 mg/kg selenium as diselenoacetic acid (Se1), diselenopropionic acid (Se2), diselenobutyric acid (Se3), or diselenodibutyric acid (Se4). Rice field eels (initial body weight 18.43 ± 0.03 g) were fed for 60 days. The Se1 group showed significantly higher WGR and SGR than the control. Whole-body crude protein was significantly increased in the Se3 and Se4 groups, while crude lipid content was significantly decreased in Se1, Se3, and Se4 groups. Selenium concentrations in the liver and kidney were highest in the Se2 group. Serum AST and ALT activities were decreased in Se4. In the Se4 group, intestinal CAT, T-SOD, and GSH-PX activities were enhanced, along with upregulation of Gpx8, CAT, Nrf2, and Keap1. Hepatic CAT and GSH-PX increased in Se2 and Se4, with Gpx8 upregulated in Se1. Intestinal lipase activity was significantly increased in Se2. At the phylum level, Proteobacteria predominated. At the genus level, Cetobacterium predominated. In summary, diselenoacetic acid enhanced growth, while diselenopropionic acid and diselenodibutyric acid improved antioxidant defense and intestinal health in rice field eel.